TOMBSTONE INSCRIPTIONS IN THE VILLAGE NAMED MALA GOSTILJA (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
This paper deals with the analysis of the inscription on the tombstone (stećak) in the village Mala Gostilja, near Višegrad. Appearance of certain let-ters, their shapes, and form can help us date this tombstone. Thanks to historical context, this tombstone can be chronologically situated at the end of 14th century and the beginning of the 15th century.
Keywords: stećak; Cyrillic script; inscription; Bosnia; Tvrtko Kotromanic; Middle Ages; XIV century